Interrogating the hybrid economy approach to Indigenous development. Issue 1 (March 2013) - Curchin, Katherine
Abstract : In the contemporary debate about remote Indigenous economic development, Jon Altman's hybrid economy approach is the major alternative to the dominant neo‐liberal perspective. Altman's approach emphasises the continuing customary economic activity of remote‐living Indigenous Australians and their legitimate aspirations to live and work on their ancestral lands. Based on a close reading of Altman's writings, this paper analyses the hybrid economy model – which is grounded in Altman's observations of outstation life in Arnhem Land – and the approach to economic development Altman derives from it. It makes explicit the numerous assumptions underpinning the hybrid economy approach to Indigenous development. Some of these assumptions are more controversial than others. It is argued that while Altman's approach celebrates the unique skills and contributions of culturally‐connected Indigenous people, it is predicated on a pessimistic assessment of the likelihood of mainstream education and employment 'closing the gap'.